Prescription errors and associated factors in patients with oncologic and hematologic diseases in a tertiary hospital - Rosa Camila Lucchetta; Bruno Salgado Riveros; Antonio Matoso Mendes; Natália Fracaro Lombardi; Wálleri Torelli Reis; Cassyano Januário Correr (São Paulo State University (UNESP), 2020)
Objective: Medication errors extend inpatient stay, increase costs and double the risk of death. Identify patients more likely to present prescription errors would be one manner that could be used to decrease the impact of such events. Thus, the present study identified the prevalence of prescription errors with patients with oncohematologic diseases and the factors associated with these events. Methods: A cross-sectional study was performed in a Brazilian tertiary hospital. Data regarding service, patients and their clinical condition, drug therapy and prescription errors were retrieved and analyzed. Results: Of 344 drug prescriptions identified, 26.2% showed at least one prescription error, mainly involving a wrong drug (48.3%). According to the logistic regression, the factors associated with errors include: presence of neutropenia OR 1.92 (95% CI 1.10-3.35), physicians on holiday or weekend shifts OR 0.40 (95% CI 0.18-0.86) and prescriptions with higher proportion of parenteral administration route OR 1.05 (95% CI 1.03-1.08). Conclusion: In conclusion, identify the factors associated with errors can be useful in developing clinical tools for predicting patients at higher risk for the occurrence of prescribing errors, as well as to contribute to the optimization of health professionals' clinical performance.